Making sense of collaboration in major infrastructure construction projects - Christoffer Rönndahl; Petra Bosch-Sijtsema; Rasmus Rempling; Mats Karlsson (Project Leadership and Society)
For complex and major infrastructure construction projects, relational governance and the importance of collaboration between project partners have led to the emergence of collaborative project delivery models. While collaboration has been studied from different perspectives, few studies focus on how collaboration is maintained and developed over time in major construction projects. Sensemaking is used as a theoretical lens to give more insight in how project actors give and make sense in relation to collaboration. Through a longitudinal case study with interviews (42) and observations, events, triggers and sensebreakers that stimulate sensemaking and sensegiving in the project are discussed. The study contributes with an empirical insight in how project actors make sense of collaboration through sensegiving, stimulating a sensemaking process while also exploring the influence of triggers and sensebreakers on this process. It underscores the dynamic and evolving nature of collaboration within the project context through sensemaking.